Pengaruh Artificial Intelligence (AI) dan Digitalisasi Terhadap Pemahaman Mahasiswa Akuntansi Tentang Laporan Keuangan - Cahyani, Dini Nur; Susilo, Dwi Ermayanti (Forum Kerjasama Pendidikan Tinggi, 2025)
This study examines the impact of Artificial Intelligence and digitalization on accounting students' understanding of financial statements. The rapid development of information technology, particularly Artificial Intelligence and digitalization, has changed the paradigm in the field of accounting. The application of this technology not only affects business practices but also has significant implications for accounting education, especially in the process of learning financial statement preparation. The aim of this research is to determine how Artificial Intelligence and digitalization affect accounting students' understanding of financial statements. The focus of this research lies on understanding the structure of financial statements, data analysis, and the ability to integrate technology into the preparation process. This research adopts a quantitative approach, using multiple linear regression analysis as the analytical tool, with data collected through questionnaires distributed to accounting students from the 2021 and 2022 cohorts using random sampling techniques. The results of the multiple regression analysis show that Artificial Intelligence (X1) has a significance value of 0.726 (> 0.05), indicating that Artificial Intelligence does not have a significant partial effect on accounting students' understanding of financial statements. On the other hand, the digitalization variable (X2) has a significance value of 0.000 (< 0.05), indicating that digitalization has a significant impact on students' understanding of financial statements. Therefore, it can be concluded that only digitalization has a significant partial effect in this model. it is expected to provide insights into students' readiness to face the challenges of digitalization and can be used to assess and develop a technology-based accounting curriculum. This study also contributes to educational institutions by aligning learning materials with the increasing digital demands in the professional world.